The majority of Norwegian patients with treatment-resistant chronic pain regained normal national health standards within 12 months after De-Qi acupuncture - a prospective observational propensity score matched study - Veronika Lindberg; Jan Baak (Frontiers in Pain Research)
PurposeIn previous studies, acupuncture was effective in the treatment of patients with chronic pain that was unresponsive to conventional therapies. However, the proportion of patients in a real-world setting who regain normal health after 1 year, following De-Qi acupuncture is unknown.MethodsThis is an observational prospective study of 354 new patients in a family medical practice between 2015 and 2018. Patients self-assessed pain using the Visual Analogue Scale (VAS), and health using the Short Form 36 Health Survey (SF-36) before treatment and at 3- and 12-months of follow-up. VAS and SF-36 components were compared for improvements and therapeutic effect sizes. Propensity score matching was employed to avoid bias by confounding variables.ResultsThe participation rate was 29%, median age 50 years (range 20–79), 65% were females, median pain duration was 18 months (6–360), the median number of acupuncture treatments was 6 (1–27). The initial VAS pain intensity of 6.2 (SD 2.5) improved to 4.0 at 3 months and 3.2 at 12 months (p < .001, large effect size); SF-36 scores also improved. 75% of patients showed strong responses, with 58% reaching complete cure and 17% achieving near-normal health. Patients aged >65 responded well and ≥6 treatments were associated with stronger responses than 1–5. Hill criteria analysis of improvements with acupuncture suggested causation over association.ConclusionIn patients with chronic pain (median 18 months), who were unresponsive to conventional treatments, De-Qi acupuncture was associated with sustained pain reduction and health improvements. Most attained Norwegian national normal health standards (complete cure) after 12-months.